Hybrid polyester and bio-polyester composites - Siti Noor Hidayah, Mustapha; Rohani, Mustapha (CRC Press, 2023)
This chapter explains the theory and concept of hybrid polyester and bio-polyester composites. The concept, parameters, and performances of multiple continuous and non-continuous systems in polyester composite are well explained in order to improve the properties of current polyester products. Multiple current hybridization approaches are discussed, including the use of multiple synthetic and bio-reinforcing fibers and fillers. In addition, the synthesis of bio-polyester through bacteria fermentation of sugars or lipid and poly(alkylene dicarboxylates) or by partial blending of synthetic polyester with vegetable oil is also discussed, along with its hybridization and applications. The interactions between the continuous and non-continuous, and between all the hybrid entities contained in the composite to allow optimum performance of polyester composite are also highlighted in this chapter. In conclusion, hybridization is the best method that could enhance the properties of polyester and bio-polyester composite to meet the high technology demand in future.